The use of cartoon illustration for the assessment of social science concepts. (November 2019) - Fradkin, Chris
The assessment of conceptual knowledge presents a challenge, particularly at the university level, at which large class size precludes individual assessment for assessment through multiple-choice examinations. This practitioner essay sets forth an alternative format: the use of cartoon illustration as a tool for the assessment of students' conceptual knowledge. The context is an upper-division (third- and fourth-year students) psychology class at an American public research university. Student artwork is included, past research is discussed, and implications for the future are considered.